Consumer Surplus From Suppliers: How Big Is It and Does It Matter for Growth? - Baqaee, David; Burstein, Ariel; Duprez, Cédric; Farhi, Emmanuel (Econometrica, 2025)
Consumer surplus, the area between the demand curve and the price, plays a key role in many models of trade and growth. Quantifying it typically requires estimating and extrapolating demand curves. This paper provides an alternative approach to measuring consumer surplus by focusing on firms as consumers of inputs. We show that the elasticity of a downstream firm's marginal cost to supplier additions and separations measures the downstream firm's consumer surplus relative to its input costs. Using Belgian data and instrumenting for changes in supplier access, we find that for every 1% of suppliers gained or lost, the marginal cost of downstream firms falls or rises by roughly 0.3%. Our estimates are directly informative about the strength of love‐of‐variety effects and the gains from movements along quality ladders. We use our microeconomic estimates of consumer surplus to assess the macroeconomic importance of supplier additions and separations in a growth accounting framework. We find that supplier churn plausibly accounts for about half of aggregate productivity growth.